1997
DOI: 10.1089/hum.1997.8.4-477
|View full text |Cite
|
Sign up to set email alerts
|

Irradiated NC Adenocarcinoma Cells Transduced with Both B7.1 and Interleukin-2 Induce CD4+-Mediated Rejection of Established Tumors

Abstract: Previous studies have shown that expression of the immune co-stimulator B7.1 reduces the tumorigenicity of some, but not all, malignant cell lines. However, B7.1-expressing tumor cells are not very effective in inducing the rejection of established tumors. This may in part be due to induction of anergy in the potentially reactive T cells. Previous studies have shown that IL-2 can reverse the anergic state both in vitro and in vivo. Therefore, we have examined the effect of retrovirus-mediated delivery and expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

1997
1997
2008
2008

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 49 publications
0
14
0
Order By: Relevance
“…A large number of studies have shown that the expression of different combinations of therapeutic genes induces a much more efficient antitumour response than expression of single genes in tumour cells. [1][2][3][4][5][6][7][8][9][10][11] However, the relative inefficiency of gene transfer procedures precludes the use of multiple vectors for the transfer and expression of different gene products. In principle, expression of several genes in a single vector can be achieved by inclusion in the vector of multiple expression cassettes each with its own independent promoter.…”
Section: Introductionmentioning
confidence: 99%
“…A large number of studies have shown that the expression of different combinations of therapeutic genes induces a much more efficient antitumour response than expression of single genes in tumour cells. [1][2][3][4][5][6][7][8][9][10][11] However, the relative inefficiency of gene transfer procedures precludes the use of multiple vectors for the transfer and expression of different gene products. In principle, expression of several genes in a single vector can be achieved by inclusion in the vector of multiple expression cassettes each with its own independent promoter.…”
Section: Introductionmentioning
confidence: 99%
“…A number of tumor models have shown that the combination of B7-1 with IL-2 is more effective than either one alone in preventing outgrowth of inoculated tumor cells. 7,8 The reasons for this are still unclear, which is perhaps not surprising given the plethora of possible effects of IL-2, including natural killer cell proliferation, 18 prevention and reversal of T-cell anergy, 19,20 and mimicry of delayed-type hypersensitivity.…”
Section: Discussionmentioning
confidence: 99%
“…8,12 Cells were cultured in Dulbecco's modified Eagle's medium containing 10% heat-inactivated fetal calf sera, 2 mM L-glutamine, 200 U/mL penicillin, and 200 g/mL streptomycin (all from Sigma).…”
Section: Vectors and Gene Transduction Protocolsmentioning
confidence: 99%
See 2 more Smart Citations